STUDY OF MANUFACTURE SOLID ORGANIC FERTILIZER FROM FISHERIES WASTE - Sofiyan Aditya; Suparmi '; Edison ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research do at November until December 2014 at Laboratorium ofFisheries Product Technology, Laboratorium of Fisheries Result Chemical,Laboratorium of Integrate and Laboratorium Ocean Chemical Faculty of Fisheriesand Marine Science University of Riau. This research aims to get the bestformulation in manufacture of solid organic fertilizer from fisheries waste. Themethod of research is experiment method, that do manufacture of solid organicfertilizer from fisheries waste. Design in non factorial of completly randomizeddesign with different formulation, which P1 (2 kg fisheries waste), P2 (3 kgfisheries waste) and P3 (4 kg fisheries waste). The parameter test us pH, moisture2JOM : OKTOBER 2015content, total nitrogen, total fosfor and total calium. The result showed that P3 isthe best treatment in maufacture of solid organic fertilizer with average value ofpH (6,85), moisture content (32,86%), total nitrogen (2,26%), total fosfor (1,44%)and total calium (0,95%).Keyword : solid organic fertilizer, fisheries waste, formulation of fisheries waste.